2002
DOI: 10.1139/x01-152
|View full text |Cite
|
Sign up to set email alerts
|

Growth and dieback of aspen forests in northwestern Alberta, Canada, in relation to climate and insects

Abstract: Trembling aspen (Populus tremuloides Michx.) is the most important deciduous tree in the Canadian boreal forest, with >1000 Tg of carbon stored in the aboveground biomass of this species. Since the early 1990s, aspen dieback has been noted over parts of the southern boreal forest and aspen parkland in western Canada. In this study, tree-ring analysis and forest health assessments were conducted in 18 aspen stands near Grande Prairie, Alta., to examine causes of reduced growth and dieback. Defoliation histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
235
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 265 publications
(249 citation statements)
references
References 28 publications
13
235
0
1
Order By: Relevance
“…The great potential for broad-scale integrated research into range changes is demonstrated by research in trembling aspen. In this species, a combination of techniques including longterm monitoring, dendroecological analyses, forest inventory data and modelling studies are being used to understand and predict range changes over broad regions of North America [7,28,48,49,72]. Remote-sensing techniques can help here, for example, with the use of indices such as the Normalized Difference Vegetation Index (NDVI), which is a good estimator of total green biomass [73].…”
Section: Methodological Difficultiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The great potential for broad-scale integrated research into range changes is demonstrated by research in trembling aspen. In this species, a combination of techniques including longterm monitoring, dendroecological analyses, forest inventory data and modelling studies are being used to understand and predict range changes over broad regions of North America [7,28,48,49,72]. Remote-sensing techniques can help here, for example, with the use of indices such as the Normalized Difference Vegetation Index (NDVI), which is a good estimator of total green biomass [73].…”
Section: Methodological Difficultiesmentioning
confidence: 99%
“…Recent studies have documented large-scale dieback events affecting hundreds or thousands of square kilometres of forest within the lowland distribution of various North American trees, including yellow cedar (Chamaecyparis nootkatentis) [46], yellow birch (Betula alleghaniensis) [47], the pinyon pine (Pinus edulis) [5] and trembling aspen [48,49] (Figure 2). Comparable dieback events are reported in Chilean cedar (Austrocedrus chilensis) at the forest-steppe ecotone in Northern Patagonia [50] and from European beech in Northern Eurasia [51], eucalypts in northeast Australia [52] and various trees and shrubs in the Mediterranean [53].…”
Section: Forest Dieback In Lowland Regionsmentioning
confidence: 99%
See 3 more Smart Citations